1993
DOI: 10.1111/j.1540-8191.1993.tb00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Current Management of the Wolff-Parkinson-White Syndrome

Abstract: In this review, we discuss the pathophysiology of the Wolff-Parkinson-White (WPW) syndrome and describe medical, surgical, and catheter based principles. WPW syndrome results from the congenital presence of impulse-conducting fascicles, known as accessory pathways (APs) or bypass tracts, which connect atria and ventricles across the annulus fibrosis and are capable of preexciting portions of the ventricular myocardium. Once triggered, atrioventricular reciprocating tachycardias (AVRTs) generally result from de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Consequently, cardiac dyssynchrony due to an accessory pathway seems responsible for such left ventricular dilation and functional impairment in accessory pathway-induced DCM. 2,6) Although flecainide, a group Ic Na channel blocker, inhibits the accessory pathway conduction in WPW syndrome, 11) to the best of our knowledge, there has been no report of the usefulness of flecainide for accessory pathway-induced DCM. Although flecainide use has been associated with an increase of proarrythmic events in adult patients with acute recurrent myocardial infarctions 12) , and with an increase in cardiovascular hospitalizations in adult patients with atrial fibrillation, 13) flecainide use has been reported effective and safe in the pediatric population 14) even in those with a reduced EF.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, cardiac dyssynchrony due to an accessory pathway seems responsible for such left ventricular dilation and functional impairment in accessory pathway-induced DCM. 2,6) Although flecainide, a group Ic Na channel blocker, inhibits the accessory pathway conduction in WPW syndrome, 11) to the best of our knowledge, there has been no report of the usefulness of flecainide for accessory pathway-induced DCM. Although flecainide use has been associated with an increase of proarrythmic events in adult patients with acute recurrent myocardial infarctions 12) , and with an increase in cardiovascular hospitalizations in adult patients with atrial fibrillation, 13) flecainide use has been reported effective and safe in the pediatric population 14) even in those with a reduced EF.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with WPW syndrome experience attacks of supraventricular tachycardia (SVT), which are triggered by changes in physical or mental conditions, and autonomic neurological states [8]. The key etiology of the SVT is the formation of a re-entry circuit of conduction waves in a heart.…”
Section: Discussionmentioning
confidence: 99%
“…3 What treatment options are available in the acute phase? 4 What is the long-term strategy in treating this condition? Answers QUESTION 1 UNDERLYING RHYTHM Atrial fibrillation with pre-excited complexes.…”
mentioning
confidence: 99%